Burden of Liver Cirrhosis in Portugal between 2010 and 2017 - Silva,João Manuel (2021)
Abstract: Introduction: Liver cirrhosis is a prevalent disease in Portugal. Recent changes in alcohol consumption, as well as the wide use of direct-acting antivirals for hepatitis C since 2015, may be contributing to changes in the national burden of liver cirrhosis in the last few years. Objectives: We aim to characterize the burden of cirrhosis in Portugal between 2010 and 2017. Patients and Methods: We analyzed all hospital admission episodes due to cirrhosis in Portugal Mainland between 2010 and 2017, registered in the national Diagnosis-Related Group database, according to etiology of cirrhosis. We also analyzed data on mortality and potential years of life lost from liver cirrhosis and chronic liver disease, retrieved from Statistics Portugal (National Institute for Statistics). Results: Between 2010 and 2017, a total of 51,438 admissions for liver cirrhosis occurred in Portugal. The annual number of admissions decreased (p= 0.044) during the analyzed period. The most frequent cause of cirrhosis was alcoholic liver disease, present in 78.9% of all admissions (n= 40,595), followed by chronic hepatitis C virus infection, present in 11.3% (n= 5,823). A male predominance was identified in the admissions for every analyzed cause of cirrhosis. Annual admissions for alcoholic cirrhosis remained stable (p= 0.075) during the 8-year period. The same stable tendency was observed in the number of admissions for cirrhosis caused by hepatitis C virus (p= 0.861) and alcohol plus hepatitis C virus infection (p= 0.082), although these admissions for hepatitis C-related cirrhosis increased until 2014-2015 and steadily decreased thereafter. Annual deaths due to liver cirrhosis and chronic liver disease decreased from 1,357 in 2010 to 1,038 in 2017 (p= 0.002). The number of potential years of life lost decreased as well in the period (p= 0.001). Conclusion: The burden of cirrhosis, evaluated by hospital admissions, mortality, and potential years of life lost, decreased in Portugal between 2010 and 2017.